Multifaceted Mechanisms of Adiponectin on Cardiovascular Health: A Comprehensive Review - Patappu, Leela; K Dhas, Priya; K.P, Mekhala; D, Ponnudhali; Jaishankar, Thirunavukkarasu; T, Saranya (Biomedical Sciences and Clinical Medicine, 2025)
Cardiovascular diseases (CVDs) remain the leading cause of mortality globally, accounting for 19.8 million deaths annually (31.0% of all fatalities). Obesity serves as an independent risk factor for CVD development through the increased production of proinflammatory adipokines due to dysfunctional adipose tissue expansion. Adiponectin, an endocrine hormone synthesized by adipose tissue, exhibits multifaceted protective mechanisms including anti-inflammatory, anti-atherogenic, and insulin-sensitizing properties. Clinical evidence from fundamental scientific research demonstrates that hypoadiponectinemia represents an independent risk factor for cardiovascular disease development. This comprehensive review examines adiponectin’s diverse mechanisms of action on cardiovascular health, encompassing its regulatory effects on carbohydrate metabolism through AMPK activation and GLUT4 translocation, lipid metabolism via PPAR pathway modulation, and anti-inflammatory responses through suppression of TNF- a and IL-6. Additionally, we discuss adiponectin’s antiatherogenic effects mediated through endothelial nitric oxide synthase enhancement and endothelial progenitor cell functionality. A better understanding of these multifaceted mechanisms could provide insights into novel therapeutic targets and biomarker applications for cardiovascular disease management. Variations in adiponectin levels can serve as valuable indicators for monitoring the effectiveness of lifestyle and pharmacological interventions aimed at improving cardiovascular outcomes.